Left ventricular strain and untwist in hypertrophic cardiomyopathy: Relation to exercise capacity - Abozguia, Khalid (Mosby, 2010)
BACKGROUND: Nonobstructive hypertrophic cardiomyopathy (nHCM) is often associated with reduced exercise capacity despite hyperdynamic systolic function as measured by left ventricular ejection fraction. We sought to examine the importance of left ventricular strain, twist, and untwist as predictors of exercise capacity in nHCM patients. METHODS: Fifty-six nHCM patients (31 male and mean age of 52 years) and 43 age- and gender-matched controls were enrolled. We measured peak oxygen consumption (peak Vo(2)) and acquired standard echocardiographic images in all participants. Two-dimensional speckle tracking was applied to measure rotation, twist, untwist rate, strain, and strain rate. RESULTS: The nHCM patients exhibited marked exercise limitation compared with controls (peak Vo(2) 23.28 ± 6.31 vs 37.70 ± 7.99 mL/[kg min], P < .0001). Left ventricular ejection fraction in nHCM patients and controls was similar (62.76% ± 9.05% vs 62.48% ± 5.82%, P = .86). Longitudinal, radial, and circumferential strain and strain rate were all significantly reduced in nHCM patients compared with controls. There was a significant delay in 25% of untwist in nHCM compared with controls. Both systolic and diastolic apical rotation rates were lower in nHCM patients. Longitudinal systolic and diastolic strain rate correlated significantly with peak Vo(2) (r = −0.34, P = .01 and r = 0.36, P = .006, respectively). Twenty-five percent untwist correlated significantly with peak Vo(2) (r = 0.36, P = .006). CONCLUSIONS: In nHCM patients, there are widespread abnormalities of both systolic and diastolic function. Reduced strain and delayed untwist contribute significantly to exercise limitation in nHCM patients.